The effects of 4-Phenylbutyric acid on ER stress during mouse tooth development - Lee, Eui-Seon; Aryal, Yam Prasad; Kim, Tae-Young; Pokharel, Elina; Kim, Ji-Youn; Yamamoto, Hitoshi; An, Chang-Hyeon; An, Seo-Young; Jung, Jae-Kwang; Lee, Youngkyun; Ha, Jung-Hong; Sohn, Wern-Joo; et al. (Frontiers in Physiology, 2023)
During tooth development, proper protein folding and trafficking are significant processes as newly synthesized proteins proceed to form designated tissues. Endoplasmic reticulum (ER) stress occurs inevitably in tooth development as unfolded and misfolded proteins accumulate in ER. 4-Phenylbutyric acid (4PBA) is a FDA approved drug and known as a chemical chaperone which alleviates the ER stress. Recently, several studies showed that 4PBA performs therapeutic effects in some genetic diseases due to misfolding of proteins, metabolic related-diseases and apoptosis due to ER stress. However, the roles of 4PBA during odontogenesis are not elucidated. This study revealed the effects of 4PBA during molar development in mice. We employed in vitro organ cultivation and renal transplantation methods which would mimic the permanent tooth development in an infant period of human. To reveal the effects of 4PBA in tooth morphogenesis, we examined the histomorphometrical changes with alterations of molecular expressions and cellular physiology during in vitro organ cultivation and renal capsule transplantation methods. Our results revealed that treatment of 4PBA altered expression patterns of enamel knot related signaling molecules, and consequently affected cellular secretion and patterned formation of dental hard tissues including dentin and enamel during tooth morphogenesis. Overall, alteration of ER stress by 4PBA treatment during organogenesis would suggest that proper ER stress is important for pattern formation during tooth development and morphogenesis, and 4PBA as a chemical chaperone would be one of the candidate molecules for dental and hard tissue regeneration.